Characterisation of coal density fractions separated from Victorian brown coal by reflux classification. (15th May 2021) - Yan, Yuxin; Qi, Ying; Marshall, Marc; Jackson, W. Roy; Stanger, Andrew; Tran, Quang Anh; Stanger, Rohan; Chaffee, Alan L.
Graphical abstract: Highlights: Separation of Victorian brown coal using reflux classifier was studied. Properties were compared with those of fractions separated by sink-float method. Higher-flow-rate fractions had higher proportions of aromatics and triterpenoids. Lower-flow-rate fractions had a higher proportion of aliphatics. Reflux classfier is beneficial for ash separation. Abstract: The work described in this paper uses a mineral-separation process to produce density fractions, which will differ in the proportions of maceral groups, and studies their physical and chemical properties. Understanding such differences in products is considered relevant to suggesting new approaches for using the immense Victorian brown coal (VBC) resource. Three run-of-mine (ROM) low-rank coals were obtained from different deposits in the Latrobe Valley, Victoria, Australia and a separation into density fractions varying in the proportions of different maceral groups of each of them has been effected using the reflux classification method. For all the three coals, the yield was highest at a water-flow rate of 20 L/min and only small yields, which may have included the purest maceral concentrates, were obtained at the highest (+40 L/min) and lowest flow rates (5 L/min). Elemental analysis and FTIR analysis showed that the lower water-flow-rate fractions had higher H/C ratios and aliphaticity than the corresponding higher water-flow-rate fractions and this was confirmed by SS 13 C NMR analysis. Py-GC–MS using a pyrolysis temperature of 650 °C demonstrated the differences in the distribution of aliphatic, aromatic and triterpenoid components in different fractions of each coal. A limited comparison was made with the properties of related fractions separated from VBC by the sink-float method.